Chapter 3 Persuasive technologies and the right to mental liberty The 'smart' rehabilitation of criminal offenders - Ligthart, Sjors (Cambridge University Press, 2022)
The outline of this chapter is as follows. In section 2 we provide a further definition of PTs, and present some possibilities that PTs offer for the smart correctional rehabilitation of criminal offenders. Next, in section 3, we briefly discuss the right to mental liberty and the extent to which this right is guaranteed by existing European human rights. In section 4, we discuss three considerations that should be relevant in specifying human rights protection against smart rehabilitation. Subsequently, in section 5 we explore whether the use of PTs in the context of smart rehabilitation would infringe an appropriately specified legal right to mental liberty. We suggest that, in this context, it might be difficult to identify compelling distinctions between novel forms of smart rehabilitation and more traditional criminal legal interventions, such as the imposition of a prison sentence or a psychological treatment program.